2014
DOI: 10.1080/0028825x.2014.898664
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization with genomic and rDNA probes reveals complex origins for polyploid New Zealand species ofPlantago(Plantaginaceae)

Abstract: The cosmopolitan plant genus Plantago contains species with a wide range of chromosome numbers in its New Zealand endemic representatives. These species are diploid, tetraploid, octoploid, decaploid, dodecaploid and 16-ploid. Using genomic in situ hybridization, we have shown that some of these polyploids contain at least three different genomes, confirming their allopolyploid status. Fluorescence in situ hybridization with 5S and 45S rDNA probes showed a wide variety of species-specific patterns of distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…All individuals from the four Hungarian populations were diploid (2 n = 2x = 12) as Soó ( 1970 ) reported previously. The characterization and physical mapping of rDNA sites in Plantago resulted in species-specific patterns (Dhar et al 2006 , 2017 ; Wong and Murray 2014 ). Each Plantago species investigated so far has unique rDNA pattern enabling discrimination of species according to the rDNA loci position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All individuals from the four Hungarian populations were diploid (2 n = 2x = 12) as Soó ( 1970 ) reported previously. The characterization and physical mapping of rDNA sites in Plantago resulted in species-specific patterns (Dhar et al 2006 , 2017 ; Wong and Murray 2014 ). Each Plantago species investigated so far has unique rDNA pattern enabling discrimination of species according to the rDNA loci position.…”
Section: Discussionmentioning
confidence: 99%
“…is 4, 5 and 6 (Peruzzi and Cesca 2002 ; Dhar et al 2006 ; Shahriari et al 2018 ). The majority of Plantago species are diploids, however, tetraploids, hexaploids, octoploids, decaploids, dodecaploids, and 16-ploids are also reported (Dhar et al 2006 ; Wong and Murray 2014 ). Previously, it was reported that P. maxima is tetraploid 2 n = 4x = 24 (Magulaev 1982 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GISH has an ability to distinguish genomic relationship of polyploids. In polyploids, GISH effectively confirmed the presumed parental genomes and in addition this technique also provides their origin information, that is, whether polyploids are alloploids or autoploids ( Table 1 ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%